Human factors in robotic assisted surgery: Lessons from studies 'in the Wild'. (July 2019) - Catchpole, Ken; Bisantz, Ann; Hallbeck, M. Susan; Weigl, Matthias; Randell, Rebecca; Kossack, Merrick; Anger, Jennifer T.
Abstract: This article reviews studies conducted "in the wild" that explore the "ironies of automation" in Robotic Assisted Surgery (RAS). Workload may be reduced for the surgeon, but increased for other team members, with postural stress relocated rather than reduced, and the introduction of a range of new challenges, for example, in the need to control multiple arms, with multiple instruments; and the increased demands of being physically separated from the team. Workflow disruptions were not compared with other surgeries; however, the prevalence of equipment and training disruptions differs from other types of surgeries. A consistent observation is that communication and coordination problems are relatively frequent, suggesting that the surgical team may need to be trained to use specific verbal and non-verbal cues during surgery. RAS also changes the necessary size of the operating room instrument cleaning processes. These studies demonstrate the value of clinically-based human factors engineers working alongside surgical teams to improve the delivery of RAS. Highlights: A wide range of system components influence, and are influenced by, robot assisted surgery (RAS). Workload is redistributed through the team while musculoskeletal stressors remain. RAS surgeries experience technology, communication, coordination, and training problems. New verbal communication forms and machine-mediated gestures may be required. Surgical and human factors collaborations can improve the delivery of RAS.